Whole Exome Sequencing Identifies Genes Associated With Non-Obstructive Azoospermia - Zhang, Hongguo; Li, Wei; Jiang, Yuting; Li, Jia; Chen, Mucheng; Wang, Ruixue; Zhao, Jing; Peng, Zhiyu; Huang, Hui; Liu, Ruizhi (Frontiers in Genetics, 2022)
Background: Non-obstructive azoospermia (NOA) affects nearly 1% of men; however, the landscape of the causative genes is largely unknown. Objective: To explore the genetic etiology which is the fundamental cause of NOA, a prospective case-control study and parental–proband trio linkage analysis were performed. Materials: A total of 133 patients with clinicopathological NOA and 343 fertile controls were recruited from a single large academic fertility center located in Northeast China; in addition, eleven trio families were available and enrolled. Results: Whole exome sequencing-based rare variant association study between the cases and controls was performed using the gene burden association testing. Linkage analysis on the trio families was also interrogated. In total, 648 genes were identified to be associated with NOA (three of which were previously reported), out of which six novel genes were found further associated based on the linkage analysis in the trio families, and involved in the meiosis-related network. Discussion and Conclusion: The six currently identified genes potentially account for a fraction (3.76%, 5 out of 133 patients) of the heritability of unidentified NOA, and combining the six novel genes and the three previously reported genes together would potentially account for an overall 6.77% (9 out of 133 patients) heritability of unidentified NOA in this study.